Melissa officinalis L. as a Nutritional Strategy for Cardioprotection - Draginic, Nevena; Jakovljevic, Vladimir; Andjic, Marijana; Jeremic, Jovana; Srejovic, Ivan; Rankovic, Marina; Tomovic, Marina; Nikolic Turnic, Tamara; Svistunov, Andrey; Bolevich, Sergey; Milosavljevic, Isidora (Frontiers in Physiology, 2021)
This review aimed to provide a summary on the traditional uses, phytochemistry, and pharmacological activities in the cardiovascular system and cardiotoxicity of Melissa officinalis (MO), with the special emphasis on the protective mechanisms in different cardiovascular pathologies. MO is a perennial aromatic herb commonly known as lemon balm, honey balm, or bee balm, which belongs to Lamiaceae family. Active components are mainly located in the leaves or essential oil and include volatile compounds, terpenoid (monoterpenes, sesquiterpenes, triterpenes), and polyphenolic compounds [rosmarinic acid (RA), caffeic acid, protocatechuic acid, quercitrin, rhamnocitrin, luteolin]. For centuries, MO has been traditionally used as a remedy for memory, cognition, anxiety, depression, and heart palpitations. Up until now, several beneficial cardiovascular effects of MO, in the form of extracts (aqueous, alcoholic, and hydroalcoholic), essential oil, and isolated compounds, have been confirmed in preclinical animal studies, such as antiarrhythmogenic, negative chronotropic and dromotropic, hypotensive, vasorelaxant, and infarct size–reducing effects. Nonetheless, MO effects on heart palpitations are the only ones confirmed in human subjects. The main mechanisms proposed for the cardiovascular effects of this plant are antioxidant free radical–scavenging properties of MO polyphenols, amelioration of oxidative stress, anti-inflammatory effects, activation of M2 and antagonism of β1 receptors in the heart, blockage of voltage-dependent Ca2+ channels, stimulation of endothelial nitric oxide synthesis, prevention of fibrotic changes, etc. Additionally, the main active ingredient of MO-RA, per se, has shown substantial cardiovascular effects. Because of the vastness of encouraging data from animal studies, this plant, as well as the main ingredient RA, should be considered and investigated further as a tool for cardioprotection and adjuvant therapy in patients suffering from cardiovascular diseases.